Plant stem cells - Greb, Thomas; Lohmann, Jan U. (Current biology, 2016)
Among the trending topics in the life sciences, stem cells have received a fair share of attention in the public debate — mostly in connection with their potential for biomedical application and therapies. While the promise of organ regeneration and the end of cancer have captured our imagination, it has gone almost unnoticed that plant stem cells represent the ultimate origin of much of the food we eat, the oxygen we breathe, as well the fuels we burn. Thus, plant stem cells may be ranked among the most important cells for human well-being. Research by many labs in the last decades has uncovered a set of independent stem cell systems that fulfill the specialized needs of plant development and growth in four dimensions. Surprisingly, the cellular and molecular design of these systems is remarkably similar, even across diverse species. In some long-lived plants, such as trees, plant stem cells remain active over hundreds or even thousands of years, revealing the exquisite precision in the underlying control of proliferation, self-renewal and differentiation. In this minireview, we introduce the basic features of the three major plant stem cell systems building on these facts, highlight their modular design at the level of cellular layout and regulatory underpinnings and briefly compare them with their animal counterparts.
Gesehen am 17.02.2017